Value of Surface Rule Coefficient (C) in Uwemanje Village, Kinovaro District, Sigi Regency - Tirtha Ayu Paramitha; Abdur Rauf; Rafiuddin Nurdin; Livawanti; Sri Rahmatia; Hasanuddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Along with the increasing population growth, the demand for water and land needs also increases. So it tends to cause changes in land use, especially forests, which will affect the water system function of a watershed. This shows that there is a need for conservation efforts to maintain the sustainability of the watershed and its water availability. Land use is a reflection of human activities on land. Land use can be detected based on the land cover. Flood disasters occur due to land use that is not suitable for its designation. Changes in land use result in changes in surface water runoff which can be known based on the coefficient of surface runoff. The greater the rain that occurs, the greater the surface flow, resulting in floods and landslides. The Uwemanje sub-watershed is a hydrological regulator as well as a source of irrigation water for the villages of Porame, Binanngga, Baliase, Boya Baliase, Padende, Sibedi and Uwemanje Alone. The Uwemanje sub-watershed has a very important role in life, especially the daily needs of the Uwemanje community as well as agriculture, animal husbandry and plantations. To find out whether the hydrological characteristics of the Uwemanje sub-watershed are getting better or worse, the flow trend of the Uwemanje sub-watershed can be seen by calculating the runoff coefficient (C), by first analyzing the discharge and rainfall. This research was conducted from April to June 2022 in Uwemanje Village, Kinovaro District, Sigi Regency, and Central Sulawesi Province. The method used to determine the value of the runoff coefficient (C) is the rational method. Based on the observations and measurements made in this study, the results showed that the area of the Uwemanje Village watershed was 12,470,000 m², daily discharge was 12,966.57 m³, rainfall was 0.07893 meters, and the runoff coefficient (C) was 0.0013. The hydrology of the water catchment area (DTA) of the Uwemanje Village is still in a stable condition, which means that the forest with its function as a water regulator has not experienced high physical disturbances.